Hubungan Tingkat Pendidikan dengan Pengetahuan Stroke pada Lansia - Mirawati, Dita; Mutnawasitoh, Asita Rohmah (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Stroke is the second leading cause of death worldwide and the third leading cause of disability. On the other hand, experience can help someone solve a problem. Stroke survivor who has learned from experience in dealing with a stroke will make more considered decisions and be more cautious when recognizing the signs and symptoms that occur in patients. The aim of this study is to determine the relationship between education level and experience with the knowledge of elderly individuals at Posyandu Laweyan. This research used a descriptive qualitative research design with a cross-sectional study design. The study was conducted at Posyandu under the supervision of the Laweyan Community Health Center. Data collection took place from March to July 2023 involving 45 respondents. The data were then analyzed using the Spearman-Correlation test to observe the relationship between experience and knowledge level. The results of the analysis showed a p-value of 0.018 (0.05); r = 0.351, indicating a significant correlation between the education level and stroke knowledge level among the elderly.